Perlindungan Hak Cipta terhadap Pengubahan Aransemen Musik Berdasarkan Undang- Undang Nomor 28 Tahun 2014 - Tiyarah Primasari Ahmad; Zamroni Abdussamad; Waode Mustika (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the protection of copyright in relation to the alteration of musical arrangements based on Law Number 28 of 2014. The research utilizes a normative research method (legal research) to examine the legal protection of altered musical arrangements in the context of internet media. Through an analysis of the relevant provisions of the law pertaining to the alteration of musical arrangements, the research aims to identify the issues that arise in practice and formulate recommendations to improve and strengthen the protection of copyright in relation to altered musical arrangements. The research identifies problems that arise in the practical implementation of copyright protection for altered musical arrangements. One common issue is copyright infringement, where the alteration of musical arrangements is done without permission or consent from the original copyright owner. Real-life cases of copyright infringement, such as the case of the song